Self-employed immigrants and their employees: Evidence from Swedish employer-employee data - Mats Hammarstedt; Chizheng Miao (Research Institute of Industrial Economics (IFN), 2018)
We present a study of immigrant self-employment in Sweden using the recent matched employer-employee data from 2014. We find large variations in self-employment rates among immigrant groups as well as between immigrants with different points for their time immigration to Sweden. High self-employment rates are found for male immigrants from the Middle East. Immigrants are less likely than natives to have employees in their firms but after controlling for firm characteristics we find that self-employed immigrants are more likely than self-employed natives to have employees. Especially non-European immigrants are more likely than natives to employ other immigrants, and even non-European and recently arrived immigrants, in their firms. Immigrants are more likely than natives to hire their spouses as employees. We conclude that self-employed immigrants play a role in the labour market integration of other immigrants. We also conclude that that the family plays a central role for self-employment activities among immigrants and that more knowledge regarding the explanations behind the results is needed.
Keywords: J61; L26; F22; J21; 330; Self-employment; Immigrants; Employment; Employees; Sweden